IMPROVING STUDENTS’ WRITING ABILITY ON DESCRIPTIVE TEXT BY USING INTENSIVE READING - Hery Nuraini; Agus Mulyana; Lutfiah Aeni (UNIVERSITAS ISLAM SYEKH YUSUF TANGERANG, 2019)
AbstrakThis research is conducted in order to improve students’ writing ability by using intensive reading at tenth grade of SMAN 14 Kabupaten Tangerang. In conducting this research the writer used qualitative descriptive as the method of the research. In this research used purposive sampling with the sample was 36 participants. To collect and analyzed the data, the writer used the information from observation, students’ writing test and interview. The result of observation and interview in this research showed that intensive reading can improve students’ writing ability on descriptive text. The result also supported by students’ writing test. It can be seen from students’ pre-test and post-test. The average score of pre-test was 30.1 or 35% and the average score of post-test was 55.4 or 65% of 36 students. The average score of post-test showed higher with increase score 25.3 or 30% of 36 students than their pre-test. It means intensive reading can improve students’ writing ability especially on descriptive text. From the result, the writer concluded that teaching writing descriptive text using intensive reading at tenth grade of SMAN 14 Kabupaten Tangerang can improve their writing ability. For the teachers and the further researchers, it is recommended that to implement this method in English classroom to improve students’ writing skill.Kata Kunci: descriptive text, intensive reading, writing ability